Erich Fromm and global public sociology - McLaughlin, Neil (Public sociology series., 2021)
Erich Fromm was one of the most influential and creative public intellectuals of the twentieth century. He was a mentor to David Riesman and an inspiration for the New Left. As the rise of global right-wing populism and Trumpism creates new interest in the kind of psycho-social writing and popular sociology that Fromm pioneered in the 1930s, this timely book tells the story of the rise, fall and contemporary revival of Fromm's theories. Drawing from empirical work, this is an invaluable contribution to popular debates about current politics, the sociology of ideas and the prospect of a truly global public sociology.